Computational method to optimize semiconductor backend processes - Kunhikannan Sachidanandan. (2008)
The objective of this project is to develop a new MS Access tool that would guide a new process engineer in a semiconductor field (backend semiconductor packaging) to optimise the process by looking into areas of parameters, materials, machine that would help to reduce the time needed for new product introduction into the manufacturing line.